Innovative Behaviour of High-Tech Internationalized Firms: Survey Results from Poland - Krzysztof Wach (Entrepreneurial Business and Economics Review, 2016)
Objective: The aim of the article is to identify and verify the relationship between internationalization and innovativeness as well as innovative behaviour of high-tech businesses in Polish context.